Microsporidia: a promising vector control tool for residual malaria transmission - Bukhari, Tullu; Pevsner, Roland; Herren, Jeremy Keith. (Frontiers in Tropical Diseases, 2022)
Long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) have resulted in a major decrease in malaria transmission. However, it has become apparent that malaria can be effectively transmitted despite high coverage of LLINs/IRS. Residual transmission can occur due to Plasmodium-carrying Anopheles mosquitoes that are insecticide resistant and have feeding and resting behavior that reduces their chance of encountering the currently deployed indoor malaria control tools. Residual malaria transmission is likely to be the most significant hurdle to achieving the goal of malaria eradication and research and development towards new tools and strategies that can control residual malaria transmission is therefore critical. One of the most promising strategies involves biological agents that are part of the mosquito microbiome and influence the ability of Anopheles to transmit Plasmodium. These differ from biological agents previously used for vector control in that their primary effect is on vectoral capacity rather than the longevity and fitness of Anopheles (which may or may not be affected). An example of this type of biological agent is Microsporidia MB, which was identified in field collected Anopheles arabiensis and caused complete inhibition of Plasmodium falciparum transmission without effecting the longevity and fitness of the host. Microsporidia MB belongs to a unique group of rapidly adapting and evolving intracellular parasites and symbionts called microsporidia. In this review we discuss the general biology of microsporidians and the inherent characteristics that make some of them particularly suitable for malaria control. We then discuss the research priorities for developing a transmission blocking strategy for the currently leading microsporidian candidate Microsporidia MB for malaria control.